Effects of electret coating technology on coronary stent thrombogenicity. (17th February 2022) - Zafar, M. Urooj; Bravo-Cordero, Jose Javier; Torramade-Moix, Sergi; Escolar, Gines; Jerez-Dolz, Didac; Lev, Eli I.; Badimon, Juan Jose
Abstract: Stent thrombosis (ST) is a catastrophic event and efforts to reduce its incidence by altering blood-stent interactions are longstanding. A new electret coating technology that produces long-lasting negative charge on stent surface could make them intrinsically resistant to thrombosis. We assessed the thrombogenicity of stents using an annular perfusion model with confocal microscopy, and determined the efficacy of electret coating technology to confer thrombo-resistant properties to standard stents. Using an annular perfusion chamber, Bare Metal Stent (BMS), standard uncoated DES (DES), and Electret-coated DES (e-DES) were exposed to human blood under arterial flow conditions. Deposits of fibrinogen and platelets on the stent surface were analyzed using immunofluorescence staining and confocal microscopy. Surface coverage by fibrinogen and platelets and the deposit/aggregate size were quantified using computerized morphometric analysis. The experimental methodology produced consistent, quantifiable results. Area of stent surface covered by fibrinogen and platelets and the average size of the deposits/aggregates were lowest for e-DES and highest on BMS, with DES in the middle. The size of fibrinogen–deposits showed no differences between the stents. The testing methodology used in our study successfully demonstrated that electret coating confers significant antithrombotic property to DES stents. These findings warrant confirmation in a larger study.